A method for preparing battery-grade lithium carbonate without water pollution

Through the comprehensive technology of acidolysis, alkaline lysis reaction, lithium ion sieve and ceramic water purification separation membrane, the problem of difficult lithium ions to extract high purity and contaminated water treatment in the prior art is solved, and efficient and environmentally friendly battery-grade lithium carbonate preparation is achieved.

CN116102038BActive Publication Date: 2025-04-08安徽鑫纪源科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310211513.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-07
Publication Date
2025-04-08
Estimated Expiration
2043-03-07

AI Technical Summary

Technical Problem

The process of extracting lithium carbonate from lithium-containing electrolytic aluminum waste slag in the prior art does not pass multiple interception or adsorption of lithium ions, making it difficult to obtain high-purity battery-grade lithium carbonate at high yields. At the same time, a large amount of contaminated water is generated during the pulping process, which increases process cost and environmental pollution.

Method used

The steps of acid dissolution, leaching, filtration, alkaline dissolution reaction, pulping filtration, carbonization post-treatment and sewage treatment are adopted, and the high-purity extraction of lithium ions and sewage purification are achieved through multiple screening of lithium ion sieves and separation of ceramic water purification membranes.

Benefits of technology

It has achieved high yield and high purity battery-grade lithium carbonate preparation, reducing water pollution and process costs, and improving the market competitiveness of the products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116102038B_ABST
    Figure CN116102038B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing battery-grade lithium carbonate without water pollution, and relates to the technical field of lithium carbonate extraction. The invention is used to solve the technical problem that high-purity battery-grade lithium carbonate is obtained with high yield without multiple interception or adsorption of lithium ions, and a large amount of polluted water is generated during the leaching and pulping process, which increases the process cost and aggravates environmental pollution if not treated. The preparation method includes acid hydrolysis, leaching, filtration, alkaline hydrolysis reaction, pulping filtration, carbonization post-treatment and sewage treatment steps. A large amount of sulfate and hydrogen fluoride gas are generated during acid hydrolysis; since a small amount of lithium ions remain in the filter residue a and the filtrate b, the lithium ion sieve can intercept the lithium ions in the filter residue c, and after the oily impurities are separated and removed by a ceramic water purification separation membrane, purified water with low impurity content can be obtained, which not only reduces water pollution in the leaching and pulping steps, but also saves the extraction cost of lithium carbonate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium carbonate extraction, and in particular to a method for preparing battery-grade lithium carbonate without water pollution. Background Art

[0002] Lithium carbonate is an inorganic compound, colorless monoclinic crystal, slightly soluble in water and dilute acid, insoluble in ethanol and acetone, and used as a raw material for ceramics, glass, ferrite, etc. Lithium is known as an important element that drives the world. With the rising global demand for clean energy, lithium's position in the market is becoming more and more important. Lithium carbonate can be divided into industrial-grade lithium carbonate and battery-grade lithium carbonate. The content of industrial-grade lithium carbonate is 99%, which can be used in ceramic glazes, special glass, semiconductor materials, etc., and can also be used in cement admixtures as a coagulation promoter; the content of battery-grade lithium carbonate is 99.5%, which is mainly used in lithium batteries. The upstream of the lithium carbonate industry chain is the collection of raw materials, which is mainly divided into lithium mines and salt lakes, and is made into industrial-grade lithium carbonate. The midstream of the lithium carbonate industry is lithium hydroxide made into lubricants, which are ultimately used in mechanical devices in downstream industries; battery-grade lithium carbonate is made into lithium batteries for electronic consumption in downstream industries; lithium hydride is made into lithium single alloys for use in downstream industries such as automobiles, aviation, and military industries; finally, high-purity lithium carbonate is directly used in downstream industries such as chemicals, glass, and pharmaceuticals.

[0003] The prior art (CN115216645A) discloses a method for extracting lithium from electrolytic aluminum waste slag by a mixed salt calcination method, which uses electrolytic aluminum waste slag as raw material, potassium and calcium salts as auxiliary materials, and adopts a mixed salt calcination method, which adopts calcification roasting, potassium salt re-calcination, alkali leaching, solid-liquid separation, freezing impurity removal, and purification processes. The content of other metal impurity ions in the leaching solution is low, and lithium salts are easily separated and extracted, and industrial lithium hydroxide and lithium carbonate are extracted and separated. The extraction rate is more than 95%, which is suitable for industrial and large-scale production, and improves the market competitiveness of the product. However, it has been found through research that the process of extracting lithium carbonate from lithium-containing electrolytic aluminum waste slag in the prior art does not obtain high-purity battery-grade lithium carbonate with high yield through multiple interception or adsorption of lithium ions. At the same time, a large amount of polluted water will be generated during the leaching and pulping process. If it is not treated, it will increase the process cost and aggravate environmental pollution. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing battery-grade lithium carbonate without water pollution, which is used to solve the technical problems that in the prior art, lithium carbonate is extracted from lithium-containing aluminum electrolytic waste slag, high-purity battery-grade lithium carbonate is obtained with high yield without multiple interception or adsorption of lithium ions, and a large amount of contaminated water is generated during the leaching and pulping process, which increases the process cost and aggravates environmental pollution if not treated.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] The present invention provides a method for preparing battery-grade lithium carbonate without water pollution, comprising the following steps:

[0007] Acid hydrolysis: Acid hydrolysis of lithium-containing aluminum electrolytic waste slag and concentrated sulfuric acid at 250-300°C to obtain a mixed solution a and hydrogen fluoride gas;

[0008] Extraction and filtration: transfer the mixed solution a to a mixer, add water for extraction, and filter through a vacuum filter to obtain filtrate a and filter residue a; the amount of water added is 2 to 3 times the mass of the mixed solution a;

[0009] Alkaline hydrolysis reaction: adding sodium carbonate to the filtrate a, carrying out alkaline hydrolysis reaction at 20-40°C, filtering with a vacuum filter to obtain a filtrate b and a filter residue b; the filter residue a and the filtrate b are passed into a mixer, adding water and stirring, and then filtering through a lithium ion sieve to obtain a filtrate c and a filter residue c;

[0010] Slurry filtration: add water to filter residue b and filter residue c to make slurry, then add lime powder for causticization reaction, filter with vacuum filter to obtain filtrate d and filter residue d;

[0011] Carbonization post-treatment: carbon dioxide is introduced into the filtrate d to carry out a carbonization reaction, and the filtrate e and filter residue e are produced by a vacuum filter, and the filter residue e is washed and dried to obtain battery-grade lithium carbonate;

[0012] Wastewater treatment: After the filtrate c and filtrate e are vacuum filtered to remove large particle impurities, they are separated and removed from oily impurities through a ceramic water purification separation membrane. The purified water obtained is transported to the mixer in the leaching and pulping steps for reuse.

[0013] As a further improved solution of the present invention, the method for preparing the ceramic water purification separation membrane comprises the following steps:

[0014] Step 1: Add 30 to 35 parts of silicon nitride powder, 4.2 to 4.8 parts of aluminum nitride powder, 12 to 15 parts of aluminum oxide powder, 1 to 3 parts of metatitanic acid, 0.6 to 1.8 parts of manganese dioxide powder, 2 to 4 parts of yttrium trioxide powder, 38 to 45 parts of N-methylpyrrolidone and 8 to 12 parts of polyphenylene ether sulfone into a planetary ball mill according to weight parts, ball mill to obtain ball mill material, and vacuum degas the ball mill material to obtain ceramic slurry;

[0015] Step 2: adding the ceramic slurry into the tape casting mold, and spreading the ceramic slurry on the tape casting backing belt during the movement of the tape casting mold to form a ceramic embryo, and immersing the ceramic embryo in water for 10 hours, taking it out to dry, and sintering it to obtain a crude ceramic water purification separation membrane;

[0016] Step three, weighing 0.8-1.2 parts of boric acid, 0.15-0.26 parts of magnesium oxide and 0.25-0.33 parts of ferric oxide by weight, using boric acid as a boron source, magnesium oxide and ferric oxide as oxidants, and ammonia as a reaction gas for chemical deposition, keeping warm at 1100-1200°C for 4 hours, and depositing a layer of boron nitride film on the surface of the crude ceramic water purification separation membrane to obtain a ceramic water purification separation membrane.

[0017] As a further improved solution of the present invention, step one is ball milling at a rotation speed of 400-600 rpm for 48 hours; step two is sintering at a high temperature of 1600-1650° C. for 4 hours.

[0018] As a further improved scheme of the present invention, the preparation method of the lithium ion sieve is as follows: 8.5-9.2g of manganese dioxide is mixed with 100mL, 1mol / L monohydrate lithium hydroxide, and stirred evenly to obtain a solid-liquid mixture, the solid-liquid mixture is transferred to a hydrothermal reactor, and the hydrothermal reactor is fixed to a homogeneous reactor, and a hydrothermal reaction is carried out at 270-280°C for 12-18 hours, centrifuged, washed with distilled water, dehydrated with anhydrous sodium sulfate, and dried at 90°C to constant weight to obtain a solid intermediate product; the solid intermediate product is placed in a muffle furnace and calcined at 350-370°C in an air atmosphere for 24 hours to obtain a layered manganese-based lithium ion sieve precursor; a lithium ion sieve is obtained by pickling with a 0.1mol / L hydrochloric acid solution, and the lithium ion sieve after adsorption saturation is adsorbed and regenerated, and the lithium ions are eluted and reused.

[0019] As a further improved solution of the present invention, the electrolytic aluminum waste slag includes the following components in mass percentage: Al 3+ 15~18%、Na + 22~26%、F - 40~50%、Li + 1~3%, SiO20.05~0.08%, Fe2O30.04~0.07%, P2O50.02~0.05%, CaO 4~7%, SO4 2- 0.2~0.5%.

[0020] As a further improved scheme of the present invention, the mass ratio of electrolytic aluminum waste slag to concentrated sulfuric acid in the acid hydrolysis step is 1:1-3, and the acid hydrolysis reaction time is 6-10 hours; the mass ratio of sodium carbonate to filtrate a in the alkaline hydrolysis reaction step is 1:3-6; and the alkaline hydrolysis reaction time is 1-2 hours.

[0021] As a further improved solution of the present invention, the amount of lime powder used in the pulping and filtering step is 0.1 to 0.2 times the sum of the masses of the filter residue b and the filter residue c; the pressure of the carbonization reaction is 2 to 4 MPa, and the time is 1 to 2.5 hours.

[0022] The present invention has the following beneficial effects:

[0023] 1. The method for preparing battery-grade lithium carbonate of the present invention comprises the steps of acid hydrolysis, leaching, filtration, alkaline hydrolysis reaction, pulping filtration, carbonization post-treatment and sewage treatment. A large amount of sulfates and hydrogen fluoride gas of Na, Al and Li are generated during acid hydrolysis, and aluminum hydroxide precipitation is generated by sodium carbonate and Al salt during alkaline hydrolysis reaction. Since a small amount of lithium ions remain in the filter residue a and the filtrate b, the lithium ions can be trapped in the filter residue c after adding water, stirring and diluting, and filtering through a lithium ion sieve. After pulping, filtration and carbonization post-treatment, high-purity battery-grade lithium carbonate can be obtained with high yield. The filtrate c generated in the alkaline hydrolysis reaction and the filtrate e generated in the carbonization post-treatment step contain fat-soluble impurities. After the oily impurities are separated and removed by a ceramic water purification separation membrane, purified water with low impurity content can be obtained. In the leaching and pulping steps, not only water pollution is reduced, but also the extraction cost of lithium carbonate is saved.

[0024] 2. In the preparation method of the ceramic water purification separation membrane of the present invention, by selecting high temperature resistant, wear resistant and impact resistant silicon nitride, heat resistant and impact resistant aluminum nitride, chemical fiber matting agent metatitanic acid, manganese dioxide with selective adsorption for lithium ions, fluorescent refractory additive yttrium trioxide, polar solvent N-methylpyrrolidone with good stability and engineering plastic polyphenylene ether sulfone with impact resistance, creep resistance and corrosion resistance, the obtained ceramic slurry has good heat resistance and impact resistance. After tape casting, a layer of hydrophobic boron nitride film is deposited on the surface of the crude ceramic water purification separation membrane, so that the ceramic water purification separation membrane has good thermal stability and chemical stability, good separation effect for oily impurities, and high retention rate for lithium ions.

[0025] 3. The preparation method of the lithium ion sieve of the present invention comprises the following steps: using a hydrothermal method to generate a solid intermediate product from manganese dioxide and lithium hydroxide monohydrate, calcining to obtain a layered manganese-based lithium ion sieve precursor, and acid washing to obtain a finished lithium ion sieve. The highly selective screening performance of the manganese-based ion sieve for lithium ions can be used to achieve secondary extraction of lithium ions and improve the yield of lithium carbonate. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 The present invention is a flow chart of the method for preparing battery-grade lithium carbonate without water pollution. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] like Figure 1 As shown, a method for preparing battery-grade lithium carbonate without water pollution in this embodiment comprises the following steps:

[0031] Acid hydrolysis: 100g of lithium-containing electrolytic aluminum waste slag and 220g of concentrated sulfuric acid are subjected to acid hydrolysis reaction at 280°C to obtain a mixed solution a and hydrogen fluoride gas; the acid hydrolysis reaction time is 9 hours; the electrolytic aluminum waste slag includes the following components in mass percentage: Al 3+ 15~18%、Na + 22~26%、F - 40~50%、Li + 1~3%, SiO20.05~0.08%, Fe2O30.04~0.07%, P2O50.02~0.05%, CaO 4~7%, SO4 2- 0.2~0.5%;

[0032] Extraction and filtration: the mixed solution a is transferred to a blender, and after extraction with water, filtered through a vacuum filter to obtain a filtrate a and a residue a. The amount of water added is 2.2 times the mass of the mixed solution a;

[0033] Alkaline hydrolysis reaction: sodium carbonate is added to the filtrate a, and an alkaline hydrolysis reaction is carried out at 30°C, and the filtrate b and the filter residue b are obtained by filtering with a vacuum filter; the filter residue a and the filtrate b are passed into a mixer, and after adding water and stirring, the filtrate c and the filter residue c are obtained by filtering through a lithium ion sieve; the mass ratio of sodium carbonate to the filtrate a is 1:5; the alkaline hydrolysis reaction time is 1.5 hours;

[0034] Slurry filtration: add water to filter residue b and filter residue c to make slurry, then add lime powder for causticization reaction, filter with vacuum filter to obtain filtrate d and filter residue d; the amount of lime powder used is 0.16 times the sum of the mass of filter residue b and filter residue c;

[0035] Carbonization post-treatment: carbon dioxide is introduced into the filtrate d for carbonization reaction, and the filtrate e and filter residue e are filtered by a vacuum filter. The filter residue e is washed and dried to obtain battery-grade lithium carbonate; the pressure of the carbonization reaction is 2.6 MPa and the time is 2 hours;

[0036] Wastewater treatment: After the filtrate c and filtrate e are vacuum filtered to remove large particle impurities, they are separated and removed from oily impurities through a ceramic water purification separation membrane. The purified water obtained is transported to the mixer in the leaching and pulping steps for reuse.

[0037] The preparation method of the ceramic water purification separation membrane comprises the following steps:

[0038] Step 1, add 32g silicon nitride powder, 4.6g aluminum nitride powder, 14g aluminum oxide powder, 1.6g metatitanic acid, 1.3g manganese dioxide powder, 2.5g yttrium trioxide powder, 40g N-methylpyrrolidone and 10g polyphenylene ether sulfone into a planetary ball mill, and ball mill at a speed of 580rpm for 48 hours, and vacuum degas the ball mill to obtain a ceramic slurry;

[0039] Step 2: adding the ceramic slurry into the tape casting mold, spreading the ceramic slurry on the tape casting backing belt during the movement of the tape casting mold to form a ceramic embryo, immersing the ceramic embryo in water for 10 hours, taking it out to dry, and sintering it at a high temperature of 1620° C. for 4 hours to obtain a crude ceramic water purification separation membrane;

[0040] Step three, weigh 1g of boric acid, 0.23g of magnesium oxide and 0.31g of ferric oxide, use boric acid as the boron source, magnesium oxide and ferric oxide as oxidants, and ammonia as the reaction gas for chemical deposition, keep warm at 1160°C for 4 hours, and deposit a layer of boron nitride film on the surface of the crude ceramic water purification separation membrane to obtain a ceramic water purification separation membrane.

[0041] The preparation method of the lithium ion sieve is as follows: 8.7g of manganese dioxide is mixed with 100mL of 1mol / L lithium hydroxide monohydrate, and stirred evenly to obtain a solid-liquid mixture, the solid-liquid mixture is transferred to a hydrothermal reactor, and the hydrothermal reactor is fixed to a homogeneous reactor, and a hydrothermal reaction is carried out at 276°C for 16 hours, centrifuged, washed with distilled water, dehydrated with anhydrous sodium sulfate, and dried at 90°C to constant weight to obtain a solid intermediate product; the solid intermediate product is placed in a muffle furnace and calcined at 360°C in an air atmosphere for 24 hours to obtain a layered manganese-based lithium ion sieve precursor; the lithium ion sieve is obtained by pickling with a 0.1mol / L hydrochloric acid solution, and the lithium ion sieve after adsorption saturation is regenerated by adsorption, and reused after eluting the lithium ions.

[0042] Example 2

[0043] like Figure 1 As shown, a method for preparing battery-grade lithium carbonate without water pollution in this embodiment comprises the following steps:

[0044] Acid hydrolysis: 100g of lithium-containing aluminum electrolytic waste slag and 120g of concentrated sulfuric acid are subjected to an acid hydrolysis reaction at 260°C to obtain a mixed solution a and hydrogen fluoride gas; the acid hydrolysis reaction time is 10 hours; the aluminum electrolytic waste slag includes the following components in mass percentage: Al 3+ 15~18%、Na + 22~26%、F - 40~50%、Li + 1~3%, SiO20.05~0.08%, Fe2O30.04~0.07%, P2O50.02~0.05%, CaO 4~7%, SO4 2- 0.2~0.5%;

[0045] Extraction and filtration: the mixed solution a is transferred to a mixer, and after extraction with water, filtered through a vacuum filter to obtain filtrate a and filter residue a; the amount of water added is 2.8 times the mass of the mixed solution a;

[0046] Alkaline hydrolysis reaction: sodium carbonate is added to the filtrate a, and an alkaline hydrolysis reaction is carried out at 25°C, and the filtrate b and the filter residue b are obtained by filtering with a vacuum filter; the filter residue a and the filtrate b are passed into a mixer, and after adding water and stirring, the filtrate c and the filter residue c are obtained by filtering through a lithium ion sieve; the mass ratio of sodium carbonate to the filtrate a is 1:4; the alkaline hydrolysis reaction time is 2 hours;

[0047] Slurry filtration: add water to filter residue b and filter residue c to make slurry, then add lime powder for causticization reaction, filter with vacuum filter to obtain filtrate d and filter residue d; the amount of lime powder used is 0.2 times the sum of the mass of filter residue b and filter residue c;

[0048] Carbonization post-treatment: carbon dioxide is introduced into the filtrate d for carbonization reaction, and the filtrate e and filter residue e are filtered by a vacuum filter. The filter residue e is washed and dried to obtain battery-grade lithium carbonate; the pressure of the carbonization reaction is 3.8 MPa, and the time is 1.2 hours;

[0049] Wastewater treatment: After the filtrate c and filtrate e are vacuum filtered to remove large particle impurities, they are separated and removed from oily impurities through a ceramic water purification separation membrane. The purified water obtained is transported to the mixer in the leaching and pulping steps for reuse.

[0050] The preparation method of the ceramic water purification separation membrane comprises the following steps:

[0051] Step 1, add 35g silicon nitride powder, 4.8g aluminum nitride powder, 15g aluminum oxide powder, 3g metatitanic acid, 1.6g manganese dioxide powder, 4g yttrium trioxide powder, 42g N-methylpyrrolidone and 11g polyphenylene ether sulfone into a planetary ball mill, ball mill at a speed of 600rpm for 48 hours, and vacuum degas the ball mill to obtain a ceramic slurry;

[0052] Step 2: adding the ceramic slurry into the tape casting mold, spreading the ceramic slurry on the tape casting backing belt during the movement of the tape casting mold to form a ceramic embryo, immersing the ceramic embryo in water for 10 hours, taking it out to dry, and sintering it at a high temperature of 1630° C. for 4 hours to obtain a crude ceramic water purification separation membrane;

[0053] Step three, weigh 1.1g of boric acid, 0.23g of magnesium oxide and 0.31g of ferric oxide, use boric acid as the boron source, magnesium oxide and ferric oxide as oxidants, and ammonia as the reaction gas for chemical deposition, keep warm at 1180°C for 4 hours, and deposit a layer of boron nitride film on the surface of the crude ceramic water purification separation membrane to obtain a ceramic water purification separation membrane.

[0054] The preparation method of the lithium ion sieve is as follows: 9.2g of manganese dioxide is mixed with 100mL of 1mol / L lithium hydroxide monohydrate, and stirred evenly to obtain a solid-liquid mixture, the solid-liquid mixture is transferred to a hydrothermal reactor, and the hydrothermal reactor is fixed to a homogeneous reactor, and a hydrothermal reaction is carried out at 280°C for 17 hours, centrifuged, washed with distilled water, dehydrated with anhydrous sodium sulfate, and dried at 90°C to constant weight to obtain a solid intermediate product; the solid intermediate product is placed in a muffle furnace and calcined at 368°C in an air atmosphere for 24 hours to obtain a layered manganese-based lithium ion sieve precursor; the lithium ion sieve is obtained by pickling with a 0.1mol / L hydrochloric acid solution, and the lithium ion sieve after adsorption saturation is adsorbed and regenerated, and the lithium ions are eluted and then reused.

[0055] Example 3

[0056] like Figure 1 As shown, a method for preparing battery-grade lithium carbonate without water pollution in this embodiment comprises the following steps:

[0057] Acid hydrolysis: 100g of lithium-containing electrolytic aluminum waste slag and 300g of concentrated sulfuric acid are subjected to acid hydrolysis reaction at 300°C to obtain a mixed solution a and hydrogen fluoride gas; the acid hydrolysis reaction time is 7 hours; the electrolytic aluminum waste slag includes the following components in mass percentage: Al 3+ 15~18%、Na + 22~26%、F - 40~50%、Li + 1~3%, SiO20.05~0.08%, Fe2O30.04~0.07%, P2O50.02~0.05%, CaO 4~7%, SO4 2- 0.2~0.5%;

[0058] Extraction and filtration: transfer the mixed solution a to a blender, add water for extraction, and filter through a vacuum filter to obtain filtrate a and residue a; the amount of water added is 3 times the mass of the mixed solution a;

[0059] Alkaline hydrolysis reaction: sodium carbonate is added to the filtrate a, and an alkaline hydrolysis reaction is carried out at 40°C, and the filtrate b and the filter residue b are obtained by filtering with a vacuum filter; the filter residue a and the filtrate b are passed into a mixer, and after adding water and stirring, the filtrate c and the filter residue c are obtained by filtering through a lithium ion sieve; the mass ratio of sodium carbonate to the filtrate a is 1:6; the alkaline hydrolysis reaction time is 1.8 hours;

[0060] Slurry filtration: add water to filter residue b and filter residue c to make slurry, then add lime powder for causticization reaction, filter with vacuum filter to obtain filtrate d and filter residue d; the amount of lime powder used is 0.2 times the sum of the mass of filter residue b and filter residue c;

[0061] Carbonization post-treatment: carbon dioxide is introduced into the filtrate d for carbonization reaction, and the filtrate e and filter residue e are filtered by a vacuum filter. The filter residue e is washed and dried to obtain battery-grade lithium carbonate; the pressure of the carbonization reaction is 4 MPa, and the time is 2.2 hours;

[0062] Wastewater treatment: After the filtrate c and filtrate e are vacuum filtered to remove large particle impurities, they are separated and removed from oily impurities through a ceramic water purification separation membrane. The purified water obtained is transported to the mixer in the leaching and pulping steps for reuse.

[0063] The preparation method of the ceramic water purification separation membrane comprises the following steps:

[0064] Step 1: add 35g silicon nitride powder, 4.6g aluminum nitride powder, 15g aluminum oxide powder, 3g metatitanic acid, 1.6g manganese dioxide powder, 3.8g yttrium trioxide powder, 44g N-methylpyrrolidone and 12g polyphenylene ether sulfone into a planetary ball mill, and ball mill at a speed of 600rpm for 48 hours, and vacuum degas the ball mill to obtain a ceramic slurry;

[0065] Step 2: adding the ceramic slurry into the tape casting mold, spreading the ceramic slurry on the tape casting backing belt during the movement of the tape casting mold to form a ceramic embryo, immersing the ceramic embryo in water for 10 hours, taking it out to dry, and sintering it at a high temperature of 1650° C. for 4 hours to obtain a crude ceramic water purification separation membrane;

[0066] Step three, weigh 1.1g of boric acid, 0.25g of magnesium oxide and 0.32g of ferric oxide, use boric acid as the boron source, magnesium oxide and ferric oxide as oxidants, and ammonia as the reaction gas for chemical deposition, keep warm at 1180°C for 4 hours, and deposit a layer of boron nitride film on the surface of the crude ceramic water purification separation membrane to obtain a ceramic water purification separation membrane.

[0067] The preparation method of the lithium ion sieve is as follows: 9.1g of manganese dioxide is mixed with 100mL of 1mol / L lithium hydroxide monohydrate, and stirred evenly to obtain a solid-liquid mixture, the solid-liquid mixture is transferred to a hydrothermal reactor, and the hydrothermal reactor is fixed to a homogeneous reactor, and a hydrothermal reaction is carried out at 280°C for 17 hours, centrifuged, washed with distilled water, dehydrated with anhydrous sodium sulfate, and dried at 90°C to constant weight to obtain a solid intermediate product; the solid intermediate product is placed in a muffle furnace and calcined at 365°C in an air atmosphere for 24 hours to obtain a layered manganese-based lithium ion sieve precursor; a lithium ion sieve is obtained by pickling with a 0.1mol / L hydrochloric acid solution, and the lithium ion sieve after adsorption saturation is adsorbed and regenerated, and the lithium ions are eluted and then reused.

[0068] Comparative Example 1

[0069] The method for preparing battery-grade lithium carbonate without water pollution in this comparative example is different from that in Example 1 in that the filtrate c and the filter residue c are not filtered through a lithium ion sieve during the alkaline hydrolysis reaction.

[0070] Comparative Example 2

[0071] The method for preparing battery-grade lithium carbonate without water pollution in this comparative example is different from that in Example 1 in that the pressure of the carbonization post-treatment step is 1.5 MPa and the time is 2 hours.

[0072] Comparative Example 3

[0073] The method for preparing battery-grade lithium carbonate without water pollution in this comparative example is different from that in Example 1 in that the sewage treatment step is eliminated.

[0074] Experimental example

[0075] For the battery-grade lithium carbonate prepared in Examples 1-3 and Comparative Examples 1-3, the product appearance was observed to be a white powder without agglomeration, and the particle size was controlled to be about 6 μm after detection. The content of lithium carbonate and other impurities was detected, and the specific test results are shown in the following table:

[0076]

[0077] It can be seen from the above table that the battery-grade lithium carbonate prepared in the embodiment of the present invention has a lithium carbonate content greater than that of the comparative example, and the contents of various impurities such as sodium, magnesium, calcium, potassium, iron, zinc, copper, and lead are all less than those of the comparative example. The method for preparing battery-grade lithium carbonate of the present invention can retain lithium ions in the filter residue c, and can obtain high-purity battery-grade lithium carbonate in high yield after pulping, filtration and carbonization post-treatment. The filtrate c produced in the alkaline hydrolysis reaction and the filtrate e produced in the carbonization post-treatment step contain fat-soluble impurities. After separation and removal of oily impurities by a ceramic water purification separation membrane, purified water with a low impurity content can be obtained, which not only reduces water pollution in the leaching and pulping steps, but also saves the extraction cost of lithium carbonate.

[0078] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0079] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing battery-grade lithium carbonate without water pollution, characterized in that: The following steps are involved: Acid hydrolysis: Acid hydrolysis of lithium-containing aluminum electrolytic waste slag and concentrated sulfuric acid is performed at 250-300°C to obtain a mixed solution a and hydrogen fluoride gas; Extraction and filtration: transfer the mixed solution a to a blender, add water for extraction, and filter through a vacuum filter to obtain filtrate a and residue a; the amount of water added is 2 to 3 times the mass of the mixed solution a; Alkaline hydrolysis reaction: add sodium carbonate to the filtrate a, carry out alkaline hydrolysis reaction at 20-40°C, filter with a vacuum filter to obtain filtrate b and filter residue b; pass the filter residue a and filtrate b into a mixer, add water and stir, and then filter through a lithium ion sieve to obtain filtrate c and filter residue c; Slurry filtration: add water to filter residue b and filter residue c to make slurry, then add lime powder for causticization reaction, filter with vacuum filter to obtain filtrate d and filter residue d, wherein the amount of lime powder is 0.1~0.2 times the sum of the mass of filter residue b and filter residue c; the pressure of carbonization reaction is 2~4MPa, and the time is 1~2.5 hours; Carbonization post-treatment: carbon dioxide is introduced into the filtrate d to carry out a carbonization reaction, and the filtrate e and filter residue e are produced by a vacuum filter, and the filter residue e is washed and dried to obtain battery-grade lithium carbonate; Wastewater treatment: After the filtrate c and the filtrate e are vacuum filtered to remove large particle impurities, the oily impurities are separated and removed by a ceramic water purification separation membrane, and the purified water obtained is transported to the mixer of the leaching and pulping steps for reuse; the preparation method of the ceramic water purification separation membrane comprises the following steps: Step 1: Add 30-35 parts of silicon nitride powder, 4.2-4.8 parts of aluminum nitride powder, 12-15 parts of aluminum oxide powder, 1-3 parts of metatitanic acid, 0.6-1.8 parts of manganese dioxide powder, 2-4 parts of yttrium trioxide powder, 38-45 parts of N-methylpyrrolidone and 8-12 parts of polyphenylene ether sulfone into a planetary ball mill according to weight parts, ball mill to obtain ball mill material, and vacuum degas the ball mill material to obtain ceramic slurry; Step 2: adding the ceramic slurry into the tape casting mold, and spreading the ceramic slurry on the tape casting backing belt during the movement of the tape casting mold to form a ceramic embryo, and immersing the ceramic embryo in water for 10 hours, taking it out to dry, and sintering it to obtain a crude ceramic water purification separation membrane; Step 3, weighing 0.8-1.2 parts of boric acid, 0.15-0.26 parts of magnesium oxide and 0.25-0.33 parts of ferric oxide according to weight parts, using boric acid as a boron source, magnesium oxide and ferric oxide as oxidants, and ammonia as a reaction gas for chemical deposition, keeping the temperature at 1100-1200° C. for 4 hours, and depositing a layer of boron nitride film on the surface of the crude ceramic water purification separation membrane to obtain a ceramic water purification separation membrane; The preparation method of the lithium ion sieve is as follows: 8.5-9.2g of manganese dioxide is mixed with 100mL of 1mol / L lithium hydroxide monohydrate, and stirred to obtain a solid-liquid mixture, the solid-liquid mixture is transferred to a hydrothermal reactor, and the hydrothermal reactor is fixed to a homogeneous reactor, and a hydrothermal reaction is performed at 270-280°C for 12-18 hours, centrifuged, washed with distilled water, dehydrated with anhydrous sodium sulfate, and dried at 90°C to constant weight to obtain a solid intermediate product; the solid intermediate product is placed in a muffle furnace, and roasted at 350-370°C in an air atmosphere for 24 hours to obtain a layered manganese-based lithium ion sieve precursor; a 0.1mol / L hydrochloric acid solution is used for pickling to obtain a lithium ion sieve, and the lithium ion sieve after adsorption saturation is adsorbed and regenerated, and the lithium ions are eluted and then reused; The electrolytic aluminum waste slag includes the following components in percentage by weight: Al 3+ 15~18%, Na + 22~26%, F - 40~50%, Li + 1~3%, SiO20.05~0.08%, Fe2O30.04~0.07%, P2O50.02~0.05%, CaO 4~7%, SO4 2- 0.2~0.5%.

2. A method for preparing battery-grade lithium carbonate without water pollution according to claim 1, characterized in that: Step 1: ball milling at a speed of 400-600 rpm for 48 hours; Step 2: sintering at a high temperature of 1600-1650° C. for 4 hours.

3. A method for preparing battery-grade lithium carbonate without water pollution according to claim 1, characterized in that: In the acid hydrolysis step, the mass ratio of electrolytic aluminum waste slag to concentrated sulfuric acid is 1:1-3, and the acid hydrolysis reaction time is 6-10 hours; in the alkaline hydrolysis reaction step, the mass ratio of sodium carbonate to filtrate a is 1:3-6; and the alkaline hydrolysis reaction time is 1-2 hours.

Citation Information

Patent Citations

  • Method for extracting lithium from electrolytic aluminum waste residues through mixed salt calcination method

    CN115216645A

  • Method for preparing aluminum fluoride and lithium carbonate by using lithium-containing aluminum electrolyte

    CN114804171A

  • Preparation method of battery-grade lithium carbonate

    CN115286017A